The Modular µSiM: A Mass Produced, Rapidly Assembled, and Reconfigurable Platform for the Study of Barrier Tissue Models In Vitro. Issue 18 (15th August 2022) - McCloskey, Molly C.; Kasap, Pelin; Ahmad, S. Danial; Su, Shiuan‐Haur; Chen, Kaihua; Mansouri, Mehran; Ramesh, Natalie; Nishihara, Hideaki; Belyaev, Yury; Abhyankar, Vinay V.; Begolo, Stefano; Singer, Benjamin H.; et al.
Abstract: Advanced in vitro tissue chip models can reduce and replace animal experimentation and may eventually support "on‐chip" clinical trials. To realize this potential, however, tissue chip platforms must be both mass‐produced and reconfigurable to allow for customized design. To address these unmet needs, an extension of the µSiM (micro device featuring a si licon‐nitride m embrane) platform is introduced. The modular µSiM (m‐µSiM) uses mass‐produced components to enable rapid assembly and reconfiguration by laboratories without knowledge of microfabrication. The utility of the m‐µSiM is demonstrated by establishing an hiPSC‐derived blood–brain barrier (BBB) in bioengineering and nonengineering, brain barriers focused laboratories. In situ and sampling‐based assays of small molecule diffusion are developed and validated as a measure of barrier function. BBB properties show excellent interlaboratory agreement and match expectations from literature, validating the m‐µSiM as a platform for barrier models and demonstrating successful dissemination of components and protocols. The ability to quickly reconfigure the m‐µSiM for coculture and immune cell transmigration studies through addition of accessories and/or quick exchange of components is then demonstrated. Because the development of modified components and accessories is easily achieved, custom designs of the m‐µSiM shall be accessible to any laboratory desiring a barrier‐style tissue chip platform. Abstract : Tissue chip platforms frequently suffer from complex and inflexible designs, limiting their adoption and distribution. To address these challenges, a modular µSiM (micro device featuring a si licon‐nitride m embrane) is developed, with easy assembly and modular functionality for quick customization by new users. Assays are developed to monitor barrier function, and interlaboratory reproducibility of a stem cell‐derived vascular model is demonstrated.